Go big or go home [large type] : the journey toward the dream - McCreery, Scotty, 1993-; Thrasher, Travis, 1971- (Center Point Large Print, 2016)
"American Idol winner Scotty McCreery shares his journey from his North Carolina roots to winning America's most popular singing competition and launching a musical career he had always dreamt about"--